The prethalamus is established during gastrulation and influences diencephalic regionalization. - Nicole Staudt; Corinne Houart (PLoS Biology)
The vertebrate neural plate contains distinct domains of gene expression, prefiguring the future brain areas. In this study, we draw an extended expression map of the rostral neural plate that reveals discrete domains inside the presumptive posterior forebrain. We show, by fate mapping, that these well-defined cell populations will develop into specific diencephalic regions. To address whether these early subterritories are already committed to restricted identities, we began to analyse the consequences of ablation and transplantation of these specific cell populations. We found that precursors of the prethalamus are already specified and irreplaceable at late gastrula stage, because ablation of these cells results in loss of prethalamic markers. Moreover, when transplanted into the ectopic environment of the presumptive hindbrain, these cells still pursue their prethalamic differentiation program. Finally, transplantation of these precursors, in the rostral-most neural epithelium, induces changes in cell identity in the surrounding host forebrain. This cell-non-autonomous property led us to propose that these committed prethalamic precursors may play an instructive role in the regionalization of the developing diencephalon.